2019
DOI: 10.4081/dr.2019.8050
|View full text |Cite
|
Sign up to set email alerts
|

Nongonococcal cervicitis: The most common cause of fluor albus in female sex workers

Abstract: Female sex workers have a high risk of suffering from sexual transmitted infections (STIs). If the female sex workers suffer from STIs, besides affecting themselves, they also have potential to transmit the disease to their clients. Fluor albus is one of the symptoms of STIs. The purpose of this research is to evaluate the type of STIs that the female sex workers suffer from. This research was conducted retrospectively on 100 female sex workers in Puskesmas Putat Surabaya in 2013-2014. The result of this resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…Cases of atypical primary syphilis misdiagnosed as pharyngeal lymphoma, tongue cancer, and other types of oral squamous cell carcinomas have been described [39][40][41]; however, the secondary stage of the disease, given the possible involvement of the whole skin area and of other organs, is the one that is most prone to misdiagnosis like palmoplantar psoriasis, psoriasis vulgaris, erythema multiforme, cutaneous lymphoma, and granulomatous diseases of the skin (annular granuloma, sarcoidosis). Moreover, involvement of internal organs with signs and symptoms of osteomyelitis, nephrotic syndrome, retinitis, and others has been reported in secondary syphilis with or without typical cutaneous/mucosal involvement, further complicating the clinical picture [42][43][44][45][46][47]. In regards to neurosyphilis, a recent narrative review revealed a low level of clinical awareness of T. pallidum infection as a possible etiology of various psychiatric disorders including dementia, delirium, depression, mania, personality changes, and psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cases of atypical primary syphilis misdiagnosed as pharyngeal lymphoma, tongue cancer, and other types of oral squamous cell carcinomas have been described [39][40][41]; however, the secondary stage of the disease, given the possible involvement of the whole skin area and of other organs, is the one that is most prone to misdiagnosis like palmoplantar psoriasis, psoriasis vulgaris, erythema multiforme, cutaneous lymphoma, and granulomatous diseases of the skin (annular granuloma, sarcoidosis). Moreover, involvement of internal organs with signs and symptoms of osteomyelitis, nephrotic syndrome, retinitis, and others has been reported in secondary syphilis with or without typical cutaneous/mucosal involvement, further complicating the clinical picture [42][43][44][45][46][47]. In regards to neurosyphilis, a recent narrative review revealed a low level of clinical awareness of T. pallidum infection as a possible etiology of various psychiatric disorders including dementia, delirium, depression, mania, personality changes, and psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…In 2010, due to the decreasing susceptibility of N. gonorrhoeae against these antimicrobials and frequent coinfection with chlamydia, a dual treatment regimen with an increased dose of cephalosporins and either doxycycline or azithromycin was recommended to curb the resistance to cephalosporins. [4][5][6][7] Nevertheless, the minimum inhibitory concentrations (MICs) of the constituents of this regimen gradually increased. In 2017-18, the WHO reported 0-21% gonococci isolates with reduced susceptibility (RS) to ceftriaxone, 0-22% with RS to cefixime and 0-60% with resistance to azithromycin worldwide.…”
mentioning
confidence: 99%